From Local To Sustainable Development On Food Security of “Kasepuhan Ciptagelar” in West Java, Indonesia - Agus M. Tauchid S; Herijanto Bekti; Nina Karlina; Ramadhan Pancasilawan (Aliansi, 2022)
This research aims to determine the extent to how indigenous peoples in West Java Province benefit from inclusive development in terms of food management during the Covid-19. Indigenous peoples have a distinct way of life, one of which is food access. Indigenous people’s system of food fulfilment ensures that they never go hungry, even during the Covid-19, which devastated many other groups. This research is critical because, in the face of fluctuating food availability and accessibility during the COVID-19, researchers aim to examine how indigenous peoples' inclusive progress in food management will enable them to meet their food demands throughout the pandemic. This research takes a unique approach in that it will examine indigenous peoples' indigenous knowledge in food management, which has an effect on the occurrence of indigenous peoples' inclusive growth and fosters their independence in all parts of life. This research employed a qualitative methodology with a descriptive approach. Qualitative research is appropriate for research on indigenous peoples' inclusive development in food management in “Kasepuhan Ciptagelar” because it can elicit additional information, data, and facts that can considerably assist researchers in addressing research questions.